RADIATION EXPOSURE DURING SPINE SURGERY USING C-ARM FLUOROSCOPY - Cristante,Alexandre Fogaça (2019)
ABSTRACT Objective: To evaluate the radiation dose received by staff in spine surgeries, including those who are not considered occupationally exposed workers. Methods: All spinal surgeries performed in the same department during a period of 12 months were evaluated with regard to the exposure of surgeons, scrub nurses, and auxiliary personnel working in the operating room to radiation from C-arm fluoroscopy. Radiation was measured by 15 film badge dosimeters placed on the professionals’ lapels, gloves, and room standardized sites. The films were analyzed in the dosimetry laboratory by collections per period. Results: During the 12 months, 81 spinal surgeries were performed by the same team, with surgical times ranging from 1 to 6 hours. The total radiation dose ranged from 0.16 mSv to 2.29 mSv depending on the dosimetry site. The most exposed site was the wrist of the main surgeon. Conclusion: The results showed that in the spinal surgeries in our setting, the radiation doses are low and within legal limits. Nevertheless, constant training of professionals is essential for radiation protection of medical staff and patients. Level of evidence I/b, exploratory cohort study.